eDNA metabarcoding: an effective tool for vertebrate diversity studies in the Colombian Amazon and Orinoco basins - Martinelli Marín, Daniela; Lasso, Carlos A.; Caballero Gaitan, Susana J. (Frontiers in Ecology and Evolution, 2024)
The development of fast, cost-effective, non-invasive, and efficient sampling alternatives, such as environmental DNA (eDNA), is crucial for understanding the changes in species biodiversity and distributions worldwide, particularly for low abundance, cryptic, and threatened species. This study utilized environmental eDNA to analyze the variety of aquatic, semi-aquatic, and terrestrial vertebrates in the Colombian Amazon and Orinoco basins. The study focused on four main subregions: Bojonawi Natural Reserve and adjacent areas (Vichada Department), Sierra de la Macarena National Park and Tillavá (Meta Department), Puerto Nariño and adjacent areas (Amazonas Department), and the Municipality of Solano (Caquetá Department). A total of 709 operational taxonomic units (OTUs) were identified across all sampling locations. The Orinoco River had the highest number of fish genera (68), while the Guayabero River had the highest number of tetrapod genera (13). New taxonomic records were found for all locations, with the highest number of previously undetected fish diversity being found in the Bita, Orinoco, and Tillavá rivers, compared to traditional surveys. Likewise, the study identified two fish species, four mammal species, and one reptile species as vulnerable. Additionally, four mammal species were identified as endangered, including the giant otter (Pteronura brasiliensis), two subspecies of the Amazon River dolphin (Inia geoffrensis geoffrensis and Inia geoffrensis humboldtiana), and the tucuxi (Sotalia fluviatilis). Standardizing the methodology and improving current DNA sequence databases for the Neotropics is essential to develop future eDNA studies and enhance our understanding of the region’s diversity.